AKAD IJARAH DALAM BISNIS SYARIAH: ANALISIS KRITIS TERHADAP IMPLEMENTASI KONTEMPORER DALAM PERSPEKTIF MAQASID SYARIAH - Fatimah Suhroh; Arbanur Rasyid (EKSYA : Jurnal Ekonomi Syariah, 2025)
Abstract This research aims to analyze the ijarah contract in sharia business, focusing on its contemporary implementation from the perspective of maqasid syariah, and evaluate its compliance with sharia principles such as justice, transparency, and economic sustainability. This research uses a normative qualitative method with a library research approach, where data is collected through documentation studies of relevant primary and secondary literature. The results of the study indicate that although the ijarah contract has a strong sharia basis and can be applied in various forms of transactions, contemporary practices such as sharia leasing and ijarah muntahiyah bi al-tamlik (IMBT) still face several problems. These include similarities with interest in conventional leasing, risk transfer to the lessee, and minimal transparency in the contract. The implication of this research is the importance of reformulation in modern ijarah practices, by emphasizing clear separation of contracts, transparency of costs, and fair risk sharing between the landlord and tenant, so that ijarah can function in accordance with maqasid syariah and contribute to sustainable economic development.